COVID-19, Carceri e “Giustizia taglia e incolla” (Balthazar, 2020)
Amidst the current pandemic, the cut-and-paste justice (the exportation of the American prison system around the world) is stronger than ever: the virus is ravaging prison populations because prisons are — and always have been — a health disaster. As a result, some countries have released a lot of people, while others have not released a single person, not to mention the suspension of prison visits and the sudden urgency for technology, which is something not all prisons were prepared for, with the obvious consequence that some people are simply denied any kind of connection to the outside world. The Writing on the Wall, an art installation made from writings by people in prison around the world, is a reminder that those people behind the wall still exist.